Laser Therapy in Hypertrophic and Keloid Scars: A Systematic Review and Network Meta-analysis - Foppiani, Jose A; Khaity, Abdulrhman; Al-Dardery, Nada Mostafa; Hasan, Mohammed Tarek; El-Samahy, Mohamed; Lee, Daniela; Abdelwahab, Omar A; Abd-Alwahed, Aya Ehab; Khitti, Huzifa Marwan; Albakri, Khaled; Lin, Samuel J (Aesthetic plastic surgery, 2024)
BACKGROUND: Laser therapy has emerged as a promising treatment modality for improving the appearance and symptoms associated with hypertrophic and keloid scars. In this network meta-analysis, we aimed to evaluate the efficacy of different laser types in treating hypertrophic and keloid scars. METHODS: A comprehensive search of four databases was conducted to identify relevant studies published up until July 2023. Data were extracted from eligible studies and pooled as mean difference (MD) for continuous outcomes and risk ratio (RR) for dichotomous data in a network meta-analysis (NMA) model, using R software. RESULTS: A total of 18 studies, comprising 550 patients, were included in the analysis. Pooling our data showed that fractional carbon dioxide (FCO2) plus 5-fluorouracil (5-FU) was superior to control in terms of Vancouver Scar Scale (VSS), pliability score, and thickness; [MD = - 5.97; 95% CI (- 7.30; - 4.65)], [MD = - 2.68; 95% CI (- 4.03; - 1.33)], [MD = - 2.22; 95% CI (- 3.13; - 1.31)], respectively. However, insignificant difference was observed among FCO2 plus 5-FU compared to control group in terms of erythema, vascularity, redness and perfusion, and pigmentation [MD = - 0.71; 95% CI (- 2.72; 1.30)], [MD = - 0.44; 95% CI (- 1.26; 0.38)], respectively. CONCLUSION: Our NMA found that the FCO2 plus 5-FU was the most effective intervention in decreasing the VSS and thickness, while FCO2 plus CO2 was the most effective intervention in decreasing the pliability score. Further research is needed to determine the optimal laser parameters and long-term efficacy of laser therapy in hypertrophic and keloid scars. LEVEL OF EVIDENCE IV: This journal requires that authors assign a level of evidence to each article. For a full description of these evidence-based medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .
Keywords: Keloid scars; Laser therapy; Cicatrix, Hypertrophic; Network meta-analysis; lidé; Hypertrophic scars; jizva hypertrofická; laserová terapie; Keloid; Treatment Outcome; Laser Therapy; výsledek terapie; keloid; Humans